ANALISA SEMIOLOGI PESAN MORAL PADA FILM “BEAUTY AND THE BEAST LIVE ACTION”: Juanna, Sholihul Abidin - Juanna Juanna; Sholihul Abidin (Prodi Ilmu Komunikasi Universitas Putera Batam, 2018)
“Beauty and The Beast Live Action” movie is a re-make film of the original version with the same title in 1991. As a romantic themed fiction show, it's no wonder that the film managed to tie the audience emotionally, so the audience can sense that they are part of the film as long as he/she watched the movie. By the time the film finishes, there will be at least a meaning or moral message that can be taken from a movie, which is composed of signs containing a moral message. Overall, the movie Beauty and The Beast Live Action gives a moral message that we should not judge a person just from his appearance alone, because the most important is the kindness of the person. However, if we look closely at the signs contained in each scene, there are still some moral messages beyond the theme of the film that we can take through semiological analysis, using qualitative research methods. This research uses Charles Sanders Peirce's semiology theory which divides the mark into three categories namely icons, indexes and symbols in creating meaning, which will then be summed up into a moral message. The object of research investigated is some snippets of scenes in the film that will be drawn conclusions of moral messages based on semiology analysis, so that ultimately obtained the results of research on what moral messages contained in every scene of the film and also that the moral message is not only obtained from the entire film alone, but also through each scene cut.